Chemical and Thermal Treatment of Dredged Sediments (Sludges): Modification of Heavy Metal Mobilities - Jocelyn Ramaroson; Souhila Kribi; Jean-Louis Dirion; Ange Nzihou; Patrick Sharrock; Guy Depelsenaire (The Minerals, Metals and Materials Society, 2008)
"This study assesses the Novosol® process, an emerging technology developed by Solvay to treat heavy metals from dredged sediments using phosphoric acid. The main goal is to convert toxic metal ions, such as Pb2+, Cd2+, Zn2+ and Cu2+ to insoluble metallic phosphates. The effectiveness of the treatment was evaluated by performing the chemical reaction in a tubular reactor, followed by convective drying and maturation of the treated sediment at ambient temperature and finally thermal destruction of the organic matter by calcinations (500°C-700°C). Selected variables (acid concentration, volume fraction of solids, flow rate, drying and calcination temperature and time) were investigated. Laboratory scale experiments were carried out with various combinations of these parameters. The influence of the quantity of acid and the temperature of calcinations on physical properties of the sediment and stabilization of the heavy metals are discussed. Introduction The French territory counts 525 000 km of rivers which transport each year on average 6 million m3 of sediments. Their deposit causes the silting of channels, rivers and lakes. This completely natural phenomenon is exacerbated by the introduction of industrial and urban wastes into the erosion and sedimentation process. This silting leads to clogging of rivers, with a reduction in their flow rates. Consecutively, other problems appear, such as flooding risks, decrease of biological purification capacity and associated loss of the biodiversity. The presence of toxic compounds (from industrial, household or agricultural origins) in the sediments worsens the situation, and requires curing to restore the natural environment and its function. The dredged sediments are either spread on agricultural land, land tipped, confined or sent for chemical or physical treatment [12]. The first research programmes on toxic sediments appeared at the end of the Eighties in the United States, in Canada, in the Netherlands and in Germany. Several techniques of treatment were developed for the sediments; these techniques can be used alone or in combination. These techniques include extraction and concentration of the pollutants: the pollutants are isolated from the sedimentary matrix and the sediment is decontaminated. In some cases of organic contaminations, the pollutants are destroyed by chemical oxidation or biodegradation and in other cases, the contaminated material is either stabilized (mixed with hydraulic binders), or destroyed (incineration) [14,15]. Phytoremediation by afforestation has also been reported [19]."